Nonlinear wave propagation in photonic crystal fibers - Haider Ali Muse; Machekhin, Yu. P.; Мачехін, Ю. П. (EUREKA: PHYSICS AND ENGINEERING, 2015)
Wave propagation is a fundamental phenomenon occurring in several physical systems. The spectra have been used by others to develop optical frequency standards. The process can potentially be used for frequency conversion in fiber optic network. In this system the dispersive properties can be controlled by the optical lattice making it possible to achieve phase-matched four wave mixing, like look the process taking place in the photonic crystal fibers (PCFs). In this paper will focus on two such systems the propagation nonlinear wave in photonic crystal fibers and the propagation of matter waves in optical lattices.
Keywords: photonic crystal fibers; nonlinear optics; propagation